CAPITAL STRUCTURE ANALYSIS TO OPTIMIZE THE PROFITABILITY OF MSMES (CASE STUDY ON MSMES HIKMAH IN SIDOARJO, EAST JAVA, INDONESIA) - Danur Ramadhani; Agus Sukoco; Joko Suyono (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the capital structure used to optimize profitability in MSME embroidery shoes. This study uses descriptive research with a qualitative approach. The analytical method is used Weighted Average Cost Of Capital (WACC). The techniques of data collection in this research used interview, observation, documentation and triangulation methods. The data that used are financial transaction records and financial statements issued by the company itself. The results showed that UD. Hikmah used the composition of the capital structure consisting of debt of 20%, 80% own capital with a ROE rate of 170%. Optimization results obtained the optimal capital structure composition on the composition of debt 23% and own capital 77%. By generating a level of profitability that can provide a favorable return for business owners, with the highest calculation of ROE that is equal to 173% and the cost of capital to be borne is Rp.18.238.000 every year.